Ramp Lesions: a Systematic Review of MRI Diagnostic Accuracy and Treatment Efficacy - José Carlos Pereira Moreira (2020)
Purpose: We conducted a systematic review of the published literature with regard to the diagnosis and treatment of ramp lesions (RLs) in Anterior Cruciate Ligament (ACL) deficient knees aiming to assess the accuracy of Magnetic Resonance Imaging (MRI), compared to arthroscopy, in establishing the presence of a RL and the clinical efficacy of surgical repair of RLs. Methods: A comprehensive search of the MEDLINE, Web of Science and Scopus databases was performed according to PRISMA guidelines. Studies assessing MRI diagnostic accuracy for RLs or the clinical effect of RL repair in participants with acute or chronic ACL injuries were included. Diagnostic accuracy measures were pooled, analysed and plotted in forest plots. Preoperative and at last follow-up treatment efficacy outcome measures were extracted and plotted in forest plots, for graphical comprehension. Results: Sixteen studies met the criteria and were included. The diagnostic analysis showed a pooled sensitivity, specificity, positive and negative likelihood ratios of 65.1% (95% CI, 59.73 to 70.42), 91.6% (95% CI, 89.14 to 94.05), 2.91 (95% CI, 2.38-3.55) and 0.53 (95% CI, 0.44-0.64), respectively, with high heterogeneity (I2 above 80%) for all measures. Treatment analysis showed improved clinical scores (Lysholm Knee Score, IKDC score and laxity difference between the knees) in all studies after meniscal suture repair. A separate analysis showed no differences between repair of smaller, stable, ramp lesions with meniscal sutures and repair with abrasion and trephination only. Conclusion: Although the results present considerable heterogeneity and quality could be improved, MRI seems to demonstrate moderate accuracy in the diagnosis of RLs in patients presenting with acute or chronic ACL tear and the surgical repair of RLs can be associated with improved overall outcomes. A continued interest in the development of knowledge of this condition is essential. Level of Evidence: III, Systematic review of Level-III studies.